2005
DOI: 10.2535/ofaj.82.83
|View full text |Cite
|
Sign up to set email alerts
|

The Appearance of Foramen in the Internal Aspect of the Mental Region of Mandible from Japanese Cadavers and Dry Skulls Under Macroscopic Observation and Three-dimensional CT Images

Abstract: Summary: The lingual canal with foramen displays different appearances on the internal surfaces of mandible as confirmed by macroscopic observation and computerized tomography (CT). The lingual canal was observed in the inside of mental region run to the outside of lingual foramen, which is extend internally from mandibular canal in right and left sides of the mandible in cadavers (13 sides out of 88 sides) and in dry skulls (43 out of 94 sides) examined. The spinal foramen connected with mental canal occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…[9][10][11][12] The sublingual and submental arteries are located in the fl oor of the mouth 17,18 and enter the mandible through these foramina. 6,10,11,[13][14][15][16] In this study, we examined the frequency and location of the lingual foramina near the midline (MLF, medial lingual foramen) and the angulation of their bony canals (MLC, medial lingual canal) on cone beam CT (CBCT) images of dry Japanese mandibles. In addition, cadavers were dissected to identify the branches of the arteries that entered the medial region of the mandible through the lingual foramina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] The sublingual and submental arteries are located in the fl oor of the mouth 17,18 and enter the mandible through these foramina. 6,10,11,[13][14][15][16] In this study, we examined the frequency and location of the lingual foramina near the midline (MLF, medial lingual foramen) and the angulation of their bony canals (MLC, medial lingual canal) on cone beam CT (CBCT) images of dry Japanese mandibles. In addition, cadavers were dissected to identify the branches of the arteries that entered the medial region of the mandible through the lingual foramina.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The mental spine is in the medial region of the lingual surface of the mandible and is surrounded by foramina connected by intraosseous canals. Various imaging and macroscopic studies have been conducted on the morphology of the lingual foramina of the mandible, [6][7][8][9][10][11][12][13][14][15][16] in part because of the increased diagnostic information gained using imaging modalities such as computed tomography (CT). Using CT, lingual foramina can be seen in the midline or canine/premolar regions of almost all mandibles.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative exams of the vital structures are essential for the safe installation of implants in the area between foramina, as well as planning for invasive procedures in this area. On the contrary, the diameter, shape and location of the lingual foramina and its canals must be investigated case by case since it varies between individuals (Yoshida et al 2005;Rosano et al;Miller et al) …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are many studies regarding location, distribution, and diameter of accessory foramina 2,[15][16][17][18] . A number of studies have reported that accessory foramina are located with highest incidence rate on the internal aspect of the mandible 2,5,10 , than on its external one.…”
Section: Discussionmentioning
confidence: 99%